2008
DOI: 10.21273/hortsci.43.3.906
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorus Rate, Leaching Fraction, and Substrate Influence on Influent Quantity, Effluent Nutrient Content, and Response of a Containerized Woody Ornamental Crop

Abstract: Production of containerized nursery crops requires high inputs of water and mineral nutrients to maximize plant growth to produce a salable plant quickly. However, input efficiencies remain below 50% resulting in major quantities of water and nutrients leached. This study was conducted to determine if production factors could be altered to increase water and phosphorus uptake efficiency (PUE) without sacrificing plant growth. The effects of a pine bark substrate amendment (clay or sand) and a 50% reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 20 publications
2
48
0
Order By: Relevance
“…For 20VC + NPK, 20VC + NK, 20VC + N, and PBS + NPK, the NUE N was 12%, 11%, 15%, and 9% and NUE P was 8%, 11%, 12%, and 7%, respectively (Tables 4 and 5). These nutrient use efficiency values are at the lower end of the ranges reported by others (Owen et al, 2008;Ristvey et al, 2007;Stoven et al, 2006). For azalea (Rhododendron var.…”
Section: Resultsmentioning
confidence: 46%
See 2 more Smart Citations
“…For 20VC + NPK, 20VC + NK, 20VC + N, and PBS + NPK, the NUE N was 12%, 11%, 15%, and 9% and NUE P was 8%, 11%, 12%, and 7%, respectively (Tables 4 and 5). These nutrient use efficiency values are at the lower end of the ranges reported by others (Owen et al, 2008;Ristvey et al, 2007;Stoven et al, 2006). For azalea (Rhododendron var.…”
Section: Resultsmentioning
confidence: 46%
“…These higher nutrient use efficiencies were associated with lower respective N and P fertilization rates. Owen et al (2008) also reported an increased NUE P from 21% to 34% when cotoneaster (Cotoneaster dammeri Schnied. 'Skogholm') grown in a pine bark sand substrate received P at a full rate and half rate, respectively.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Among these Mediterranean species, kneeholy and confetti tree are widely grown for their commercial value (Lopez, 2004;Veronese, 2014). Although there are a number of publications that have investigated the reuse of runoff water in nursery production (Owen et al, 2008;Polomski et al, 2005Polomski et al, , 2008, little is known about reusing irrigation water for the production of confetti tree. A greenhouse experiment was conducted to determine the effects of different irrigation treatments on biomass, mineral composition, and photosynthetic parameters of this species.…”
mentioning
confidence: 99%
“…Research has related plant water use to plant growth index and pan evaporation (Knox, 1989) or growth index and leaf area (Nui et al, 2006), which were shown to be good descriptors of water use for multiple species. Maintenance of specific leaching fractions has also been used to adjust irrigation in response to increasing plant size (Owen et al, 2008). However, these methods do not adjust to day-to-day changes in weather.…”
mentioning
confidence: 99%